Ontogenetic morphometrics in Psammolestes arthuri (Pinto 1926) (Reduviidae, Triatominae) from Venezuela - Goncalves, Lisseth (2015)
Psammolestes arthuri is a secondary Chagas disease vector associated with bird nests in the peridomicile. We studied the head architecture to describe the size changes and conformation variation in the P. arthuri instars. Were collected and reared 256 specimens associated with Campylohynochus nucalys nests in Guarico state, Venezuela. We photographed and digitized ten landmarks coordinate (x, y) on the dorsal head surface; then the configurations were aligned by Generalized Procrustes Analysis. Canonical Variates Analysis (CVA) was implemented with proportions of re-classified groups (=instars) and MANOVA. Statistical analysis of variance found significant differences in centroid size (KruskalWallis). We found gradual differences between the 1st instar to 5th and a size reduction in the adults; the CVA showed significant separation, and a posteriori re-classification was 50-78% correctly assigned. The main differences could be associated with two factors: one related to the sampling protocol, and another to the insect morphology and development.